Behavioral and neurobiological implications of kairomones for rodents: an updated review - Manjunath, Diya; Sampath, Hayavadhan; Kirkwood, Roy N.; Santhosh, Sinsha; Sankarganesh, Devaraj (Frontiers in Neuroscience, 2025)
Like many other vertebrates, rodents communicate via pheromones, which favors intraspecies communication. In contrast, kairomones are semiochemicals involved in interspecific communication, facilitating information between organisms of different species but advantageous for the receiver. Kairomones induce behavioral, physiological, and endocrinological changes in rodents, and have been proven to activate specific neuronal pathways in one or multiple components of the olfactory system (the main olfactory system, accessory olfactory system, and Gruenberg ganglion). The sophisticated olfactory networks help rodents innately recognize kairomones and elicit appropriate behavioral (aversive, avoidance, defense, and escape mechanisms), physiological, and endocrinological changes. Thus far, odor sources (e.g., urine, feces, hair, and body rubbings) of predators, such as felines, canines, and serpentes, have been studied in rodents. Specific kairomones have been identified, behaviorally tested, and validated for their potential to induce behavioral, neuronal, and endocrinological changes in rodents. One of the most studied kairomones is the fox odor, 2,5-dihydro 2,4,5-trimethylthiazoline, although other compounds have been reported to a limited extent. This review summarizes the current knowledge on kairomones and their effects on the behavioral, neuronal, and endocrine systems of rats and mice.